FAKTOR KEUANGAN YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN MAKANAN DAN MINUMAN DENGAN MODEL ALTMAN Z-SCORE - Susanto, Russel Andama; Salim, Susanto; Daryatno, Andreas Bambang (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study was to analyze empirically the effect of the variables in the Altman Z-Score method, namely Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest and Tax to Total Assets, Market Value Equity to Total Liabilities, and Sales to Total Asset on Financial Distress in food and beverage company listed on the Indonesia Stock Exchange in 2020-2022. The results of this study indicate that Working Capital to Total Assets has a positive not significant impact on financial distress, different from Retained Earnings to Total Assets, Market Value Equity to Total Liabilities, and Sales to Total Asset that have a significant positive impact on financial distress and Earnings Before Interest and Tax to Total Assets have a negative not significant impact on financial distress.